Becoming the ex-wife the unconventional life and forgotten writings of Ursula Parrott - Gordon, Marsha 1971- (University of California Press, 2023)
"Becoming the Ex-Wife tells the story of US women's changing prospects in early twentieth-century life through the lens of its once-famous but now-forgotten subject, Ursula Parrott. Parrott was a prolific and best-selling author whose books, Hollywood deals, quartet of marriages and divorces, and numerous run-ins with the law made headlines over the course of her unconventional life. Part biography, part cultural history, Becoming the Ex-Wife is a timely story about women and careers, divorce, reproductive rights, and single motherhood told through the life of a woman who was on the front line of a culture war that is still being fought today"--
Includes bibliographical references and index
Keywords: Parrott, Ursula -- 1899-1957; Geschichte 1900-2000; Literaturkritik; Autorin; Biografie; Parrott, Ursula / 1899-1957 / Biography; Authors / 20th century / Biography; Women / Social conditions / 20th century; Parrott, Ursula / 1899-1957; Authors; Women / Social conditions; 1900-1999; Biographies